(untitled) (Journal of Comparative Social Work, 2013)
This article considers the meaning of the participants’ home as an interview context when studying sensitive family issues. The article is based on two qualitative family studies by the authors on foster children’s perspectives on their home and their family relations and client families’ experiences of preventive family support. Both studies address sensitive family issues, in particular Finnish child welfare. The first author’s interview data consist of interviews with foster children, social network maps and diaries and the second author’s data of interviews with six client families. Most of the interviews were conducted at the participants’ homes, but in the second author’s study two interviews were conducted at the university.